Right of access to information and its limitation by national security in Nigeria: mutually inclusive or exclusive? - Salau, Aaron Olaniyi (Department of Public Law, 2017)
Section 39(1) of the 1999 Constitution of Nigeria guarantees freedom of expression, including the right to receive and impart information. Also, the domestication of the African Charter on Human and Peoples' Rights' makes the Charter's protections for access to information part of Nigerian law. Indeed, sections 39(3) and 45(1) of the Constitution permit restrictions on access to information, but only by 'law that is reasonably justifiable in a democratic society'. Unfortunately, access to information in Nigeria is heavily circumscribed by statutes that confer absolute powers on the executive to classify information to protect vague 'national security' interests inconsistently with what is reasonably justifiable in a democratic society. Underlying this problem are a colonial legacy of administrative secrecy that disdains disclosure of official information and clumsy constitutional rights provisions that accentuate security restrictions rather than the right to information. Using democratic theory as an analytical tool, this thesis advocates for the right of access to information as not just a constitutional value, but also a minimum requirement for the functioning of a democratic society. In so doing, it aims to curtail abuse of executive powers under national security laws that permit limitations on access to information. The thesis uses African human rights standards of reasonableness to evaluate how national security laws that limit access to information measure against constitutional standards of reasonableness and justifiability in a democratic society. The thesis finds that constitutional protection and jurisprudential recognition of the right of access to information in Nigeria do not comply with minimum international law requirements. The thesis ultimately suggests that limitation of access to information on grounds of national security must be in the public interest. In striking a balance between access to information and national security, it recommends a sufficient legislative description of 'national security' and clear constitutional framework for access to information, subject to restrictions only where harm to national security is demonstrably greater than access to information.